Un yo solo, mudo e inmóvil: la narración de la enfermedad y de sus consecuencias sociales en Las mutaciones de Jorge Comensal (Altre Modernità, 2020)
In the novel Las mutaciones, Jorge Comensal describes perfectly the mechanisms that lay behind the acceptance or rejection, both individual than collective, that starts after a diagnosis of illness. After knowing that he has a cancer – a rabdomiosarcoma typical of the children age – Ramón’s life collapses. His personal and professional relations are upset and Ramón becomes a motionless testimony of the mutations that his illness brings in all the areas of his life. Thanks to the use or irony and a simple but effective delineation of characters Comensal is able to describe the social frustration that the diagnosis of illness brings inner and outer the life of the sick. This study aims to outline how Comensal’s novel shows the distance between curation and person in contemporary medicine and to analyze how, thanks to a specific structure of the novel and through the development of the topic of communication, the author starts a reflection about how illness can modify our lives. The theoretical base is represented by the concept of “mindful body” (Scheper Hughes - Lock) and by the concept of illness as a more or less acceptable metaphor for the community defined by Sontag.
Keywords: Las mutaciones; Cáncer; Cuerpo pensante